Mapping Smart Regions. An Exploratory Approach - Occelli, Sylvie; Sciullo, Alessandro (TeMA - Journal of Land Use, Mobility and Environment, 2014)
The paper presents the results of an exploratory approach aimed at extending the ranking procedures normally used in studying the socioeconomics determinants of smart growth at the regional level. Most of these studies adopt a methodological procedure which essentially consists of the following steps: a) identification of the pertinent elementary indicators according to the study objectives; b) data selection and processing; c) combination of the elementary indicators by multivariate statistical techniques aimed at obtaining a robust synthetic index to rank the observation units. In the procedure a relational dimension is mainly subsumed in the system oriented perspective adopted in selecting the indicators which would best represent the system determinants depending on the goals of the analysis (step a). In order to get deeper insights into the smartness profile of the European regions, this study makes an effort to account of the relational dimension also in steps b and c of the procedure. The novelties of the proposed approach are twofold. First, by computing region-to-region distances associated with the selected indicators it extends the conventional ranking procedure (step c). Second, it uses a relational database (step b), dealing with the regional participation to the FP7-ICT project, to modify the distances and investigate its impact on the interpretation of the regional positioning. The main results of this exercise seem to suggest that regional collaborations would have a positive role in regional convergence process. By providing an opportunity to get contacts with the areas endowed with a comparatively more robust smartness profile, regions may have a chance to enhance their own smartness profile.